2020
DOI: 10.3389/fonc.2020.00761
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Carboplatin With 5-Fluorouracil vs. Cisplatin as Concomitant Chemoradiotherapy for Locally Advanced Head and Neck Squamous Cell Carcinoma

Abstract: Background: Chemoradiotherapy (CRT) including three cycles of cisplatin is considered the standard of care for locally advanced head and neck squamous cell carcinoma (LA-HNSCC). However, around one-third of the patients cannot complete cisplatin because of toxicity. Carboplatin plus 5-fluorouracil (carbo-5FU) is another accepted treatment option with a different toxicity profile. We compared tolerability and efficacy of concomitant carbo-5FU and cisplatin. Patients and Methods: We conducted a retrospective ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Head and neck cancers have globally affected more than 5.5 million people and have caused about 379,000 deaths [21]. The majority of the squamous cell carcinomas occur in the head and neck region [22].…”
Section: Resultsmentioning
confidence: 99%
“…Head and neck cancers have globally affected more than 5.5 million people and have caused about 379,000 deaths [21]. The majority of the squamous cell carcinomas occur in the head and neck region [22].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, adherence was lower with carboplatin + 5-fluorouracil, possibly because of its higher rates of toxicity. 50 A meta-analysis also showed that OS was shorter with carboplatin than with cisplatin, with more hematologic toxicity and mucositis. 51 …”
Section: Suitability For Cisplatin Chemotherapymentioning
confidence: 99%
“…In addition, adherence was lower with carboplatin + 5-fluorouracil, possibly because of its higher rates of toxicity. 50 A meta-analysis also showed that OS was shorter with carboplatin than with cisplatin, with more hematologic toxicity and mucositis. 51 Clinical evidence supporting the cetuximab use as an alternative to cisplatin in locally advanced disease was provided by a phase III study, in which the use of radiotherapy with or without cetuximab was evaluated.…”
Section: Alternative Treatments To High-dose Cisplatin Locally Advanced Diseasementioning
confidence: 99%
“…Superior OS was reported with CRT using cisplatin as compared to using Cetuximab 15,16 . Treatment with cisplatin was found to result in survival outcomes that are comparable to those with carboplatin in some studies, 8,10,26 but to be superior to carboplatin in others, whether the latter was used alone 27 or with 5‐FU 28 . Compared to CRT with LDC, CRT with HDC was reported to have either greater 1,3,11,24 or comparable 13 toxicity profile, or even lower acute toxicity 21 .…”
Section: Introductionmentioning
confidence: 99%